Development of an attitude scale for occupational health and safety (International Journal of Occupational Safety and Health, 2026)
Introduction: The concept of occupational health and safety has become one of the most fundamental issues in today's working life. This concept, which has extremely important implications in human, economic, legal and social dimensions, has created an important field of research in the scientific arena. The aim of this study is to develop an attitude scale towards occupational health and safety, which is one of the most current issues in working life.Methods: In this study, scale design technique, one of the quantitative research methods, was used. The study was conducted on 554 blue-collar workers employed at two factories operating in the ceramics and forest products sectors in the Çanakkale Çan Organised Industrial Zone.Results: A draft scale consisting of 50 items was developed. Exploratory factor analysis was performed with data collected from 277 participants, and the scale completed the EFA analysis with 34 items and 4 sub-factors.Conclusion: As a result of the study, the Attitude Scale Towards Occupational Health and Safety was developed, consisting of four sub-factors (personal, management, education, and work environment) and 32 items.